2016
DOI: 10.1038/ncomms11702
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-initiating cell-specific miR-1246 and miR-1290 expression converge to promote non-small cell lung cancer progression

Abstract: The tumour-initiating cell (TIC) model accounts for phenotypic and functional heterogeneity among tumour cells. MicroRNAs (miRNAs) are regulatory molecules frequently aberrantly expressed in cancers, and may contribute towards tumour heterogeneity and TIC behaviour. More recent efforts have focused on miRNAs as diagnostic or therapeutic targets. Here, we identified the TIC-specific miRNAs, miR-1246 and miR-1290, as crucial drivers for tumour initiation and cancer progression in human non-small cell lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(173 citation statements)
references
References 66 publications
7
166
0
Order By: Relevance
“…Since TIC cells are essential for tumor initiation, tumor maintenance, and tumor growth (Cheng & O'Neill, 2009; Ricci‐Vitiani et al , 2009; Grinshtein et al , 2011; Beck & Blanpain, 2013; Bansal et al , 2016; Zhang et al , 2016), increased TIC activity is expected to accelerate tumor growth in vivo (Grinshtein et al , 2011; Beck & Blanpain, 2013; Bansal et al , 2016). To test the effect of FUT9 on this process, we generated a xenograft model of colorectal cancer in immune‐deficient NOD/SCID gamma mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since TIC cells are essential for tumor initiation, tumor maintenance, and tumor growth (Cheng & O'Neill, 2009; Ricci‐Vitiani et al , 2009; Grinshtein et al , 2011; Beck & Blanpain, 2013; Bansal et al , 2016; Zhang et al , 2016), increased TIC activity is expected to accelerate tumor growth in vivo (Grinshtein et al , 2011; Beck & Blanpain, 2013; Bansal et al , 2016). To test the effect of FUT9 on this process, we generated a xenograft model of colorectal cancer in immune‐deficient NOD/SCID gamma mice.…”
Section: Resultsmentioning
confidence: 99%
“…TICs represent a higher proportion of the overall cell population in a tumor at earlier stages of tumor development. At later stages however, TICs are gradually outgrown by the rest of the tumor cells (Fig 4E), but they are still required for efficient tumor growth and maintenance (Cheng & O'Neill, 2009; Ricci‐Vitiani et al , 2009; Grinshtein et al , 2011; Beck & Blanpain, 2013; Bansal et al , 2016; Zhang et al , 2016). Since our experimental data suggest that FUT9 provides an advantage for TIC populations, while its reduced activity benefits other tumor cells, its relative abundance should be expected to gradually drop with tumor progression, mirroring a decrease in the proportional representation of TICs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang et al . (2016) report that miR‐1246 and miR‐1290 were overexpressed in serum samples of patients with non‐small‐cell lung cancer (NSCLC) when compared to healthy individuals. After overexpression of these miRNAs in lung epithelial cells, ectopic overexpression of miR‐1246 repressed PRL36A , GLIPR1 , HAS2 , NCKAP5 , MT1G, and CYP4F11 , whereas overexpression of miR‐1290 repressed MT1G , MT1H , GLIPR1 , CYP4F11, and NCKAP5 (Zhang et al ., 2016).…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%
“…Furthermore, they identified the putative tumor suppressor MT1G as a direct target of miR‐1246 and miR‐1290 [76]. Their observations indicate that miR‐1246 and miR‐1290 can behave as noninvasive biomarkers that may be used for the early detection of lung cancer (Zhang et al ., 2016). Finally, Zhu et al .…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%
“…Additionally, exosomal microRNAs may endow recipient cells with resistance to chemotherapy. Among all miRNAs investigated, miR-1246 has drawn much attention and has been found to function as a proto-oncogene in lung and other cancers [4, 5]. Recently, it was reported that miR-1246 was strongly up-regulated in breast cancer [6].…”
Section: Introductionmentioning
confidence: 99%